Transformasi Birokrasi Digital melalui Inovasi Kebijakan : Studi Kualitatif atas Implementasi Aplikasi M-Paspor di Indonesia - Kirana Anindya Saffa; Annaera Arastha; Ghaisani Fazilatunnisa; Muhammad Fatih Al Kutsar; Firman Lukman (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Digital bureaucratic transformation has become a crucial component of public administration reform in Indonesia through the utilization of technology to enhance public services. This study examines the implementation of the M-Paspor application as one of the strategic policy innovations in the immigration sector. The application was developed as a solution to problems found in the conventional service system. M-Paspor simplifies the passport application procedures, increases bureaucratic effectiveness and efficiency, and strengthens accountability in public service delivery. The presence of M-Paspor has brought significant changes to the structure and work system within the Directorate General of Immigration. However, its implementation still faces various challenges, including unequal digital access, limited infrastructure, low digital literacy among civil servants, and resistance to changes in bureaucratic work culture. This study uses a descriptive qualitative approach based on literature review, with sources selected using search strings tailored to the research objectives. The results of this study are expected to serve as a reference for further discussions regarding the benefits, challenges, and sustainability of M-Paspor in supporting the broader digitalization of public service programs in Indonesia.